Critical Wounds, Sutured - Horváth, Imre Olivér (Hungarian Journal of English and American Studies, 2021)
Book review:Veprinska, Anna. Empathy in Contemporary Poetry after Crisis. London: Palgrave Macmillan, 2020. 203 pages. ISBN 978-3-030-34319-4. Hb. €74.89.